Implementasi Penertiban Organisasi Kemasyarakatan di Lampung oleh Badan Kesatuan Bangsa dan Politik Provinsi Lampung - Indah Satria (PRANATA HUKUM, 2018)
Mass organizations registered with The National Unity and Politics Agency of Lampung Province are not in accordance with the number of mass organizations currently in Lampung Province which means that there are still many mass organizations that are not yet registered with The National Unity and Politics Agency of Lampung Province. The problem in this study is how is the implementation of Mass Organization Control in Lampung by The National Unity and Politics Agency? and what are the obstacles in the implementation? The results of this study, namely the implementation of controlling mass organizations in Lampung at this time is still not optimal due to the obstacles faced, namely the limited number of employees of the Lampung Province The National Unity and Politics Agency, limited budget, not yet optimal socialization of regulations, facilities and infrastructure has not been maximized, lack of public awareness, lack of knowledge of the management of mass organizations regarding the obligation to register their organizations.